1990
DOI: 10.2307/1510390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interactive Vocabulary Instruction on the Vocabulary Learning and Reading Comprehension of Junior-High Learning Disabled Students

Abstract: Drawing upon theory-driven vocabulary instruction and the vocabulary-reading comprehension connection, this study compared the effectiveness of three interactive vocabulary strategies derived from the knowledge hypothesis with definition instruction derived from the access and instrumental hypotheses. Subjects were 61 learning disabled junior-high students. Using content-area texts, students participated in one of three interactive strategies — semantic mapping (SM), semantic feature analysis (SFA), and semant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
133
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(133 citation statements)
references
References 21 publications
0
133
0
Order By: Relevance
“…This publication is annotated and indexed by the ERIC Clearinghouse on Handicapped and Gifted Children for publication in the monthly Current Index to Journals in Education (CIJE) assumption is that integration of instructional devices (e.g., graphic organizers) allows teachers to select, organize, and present difficult to understand material and make the text more meaningful and accessible to students of varying ability levels, including students with LD. Research indicates that instruction using graphic organizers and matrices that visually depict relationships between ideas (e.g., Bos & Anders, 1990;DiCecco & Gleason, 2002), advance organizers that prepare students for an upcoming lesson (e.g., Darch & Gersten, 1986), story maps that emphasize story grammar elements in narrative texts, outlines and study guides that highlight critical information (e.g ., , mnemonic illustrations that make the information more memorable (e.g., , and computer assisted instruction that provides opportunities for independent review and practice ( e.g., Okolo & Feretti, 1996) increase text comprehension and recall for students with LD.…”
Section: Exce_ntional Childrenmentioning
confidence: 99%
“…This publication is annotated and indexed by the ERIC Clearinghouse on Handicapped and Gifted Children for publication in the monthly Current Index to Journals in Education (CIJE) assumption is that integration of instructional devices (e.g., graphic organizers) allows teachers to select, organize, and present difficult to understand material and make the text more meaningful and accessible to students of varying ability levels, including students with LD. Research indicates that instruction using graphic organizers and matrices that visually depict relationships between ideas (e.g., Bos & Anders, 1990;DiCecco & Gleason, 2002), advance organizers that prepare students for an upcoming lesson (e.g., Darch & Gersten, 1986), story maps that emphasize story grammar elements in narrative texts, outlines and study guides that highlight critical information (e.g ., , mnemonic illustrations that make the information more memorable (e.g., , and computer assisted instruction that provides opportunities for independent review and practice ( e.g., Okolo & Feretti, 1996) increase text comprehension and recall for students with LD.…”
Section: Exce_ntional Childrenmentioning
confidence: 99%
“…Research has shown that the use of diagrams benefits learning as they promote greater recall, comprehension, and vocabulary learning (Bos & Anders, 1990) and improve reading comprehension in students with learning disabilities (Ae-Hwa, Vaughn, Wanzek, & Wei, 2004). In a study carried out by Idol and Croll (1987), five intermediate-level, elementary students with mild learning handicaps and poor comprehension were trained to use story-mapping procedures as a schema-building technique to improve reading comprehension.…”
Section: Association With a Topicmentioning
confidence: 99%
“…Cognitive maps make "use of lines, arrows, and spatial arrangements to describe text content, structure, and key conceptual relationships" (Darch & Eaves, 1986 , p. 310), thereby making implicitly stated relationships explicit and diffi cult to understand information more memorable. While several researchers have successfully used teacher constructed cognitive maps and documented gains on reading comprehension for students with LD (Bos & Anders, 1990 ;Darch & Eaves, 1986 ), research on teaching students to independently generate cognitive maps is limited. Boyle ( 1996 ) examined the effects of instruction in a cognitive mapping strategy on the literal and inferential comprehension skills of middle school students with LD and those with mild cognitive disabilities.…”
mentioning
confidence: 99%